PROTOTYPE SISTEM KATALOG BUKU ONLINE MENGGUNAKAN TEKNOLOGI JAVA DAN XML UNTUK PERANGKAT SELULER - Yusuf Anshori (Foristek, 2012)
Libraries as providers of information that is generally in the form of print media (books, reports, magazines, newspapers, journals, etc.) should gradually improve its services so that remain attractive to the visitors. One of the service improvements that can be done is to provide an information catalog that can be accessed by telecommunications media such as mobilephone and smart phone. This paper aims to create a prototype of the online book catalog system software using Java and XMLtechnology and use wireless networking technology from the hardware catalog of books that can be accessed by cellular telephone communication media in particular. By inspecting the testing results conducted in this study known that the catalog is accessible for cellular phones from various vendors.